ANALISIS KETERLAKSANAAN LAYANAN BIMBINGAN DAN KONSELING SMP NEGERI DI KOTA SAMPIT - Agus Heriyanto; Jayadi Jayadi; Aulia Rahmadani (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
This study aims to determine the implementation of Guidance and Counseling services Junior High School in the city of Sampit. This type of study is descriptive qualitative. The subject of this study is the counseling teachers. The collection techniques used are interviews, observation and documentation. The were analyzed through data reduction this study using triangulation techniques sources and methods.The study results show that the analysis of the implementation of Guidance and Kounseling junior high schools in Sampit in at Baamang and Ketapang can be concluded that the implementation of Guidance and Counseling services Junior High School in Sampit as a whole enough optimal.